The scope of the Old Testament and the nature of its theology : determining the object and subject of Old Testament theology by means of the Septuagint - Kotze, Gideon Rudolph (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MTh (Old and New Testament))--Stellenbosch University, 2006.